2017
DOI: 10.1080/03079457.2017.1341622
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to develop a detection method specific for virulent duck plague virus strains based on the UL2 gene B fragment

Abstract: A comparison of the unique long region 2 (UL2) gene sequences between 10 virulent and 11 attenuated duck plague virus (DPV) strains (including all DPV UL2 gene sequences registered in GenBank) showed that the UL2 genes in the attenuated DPV strains had a 528 bp deletion in the B fragment. Primers were designed based on the B fragment sequence of the UL2 gene in an attempt to establish a fluorescence quantitative polymerase chain reaction (PCR) and a conventional PCR detection method that could specifically det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…DPV genomes from different countries are highly homologous to each other, but can be categorized into virulent and attenuated strains based on a number of virulence-related genes ( Aasdev et al, 2021 ). It has been reported that the UL2 gene predicted to encode uracil DNA glycosylasewhich play an important role in viral replication, and is significantly different between virulent and attenuated strains ( Xie et al, 2017 ). The UL2 gene of SD423 was analyzed and was identical to the Chinese, European and Indian strains; There is a large difference with the attenuated strain DEV K p63 ( Zou et al, 2014 ), SD423 has a 529 bp insertion after 281 bp.…”
Section: Discussionmentioning
confidence: 99%
“…DPV genomes from different countries are highly homologous to each other, but can be categorized into virulent and attenuated strains based on a number of virulence-related genes ( Aasdev et al, 2021 ). It has been reported that the UL2 gene predicted to encode uracil DNA glycosylasewhich play an important role in viral replication, and is significantly different between virulent and attenuated strains ( Xie et al, 2017 ). The UL2 gene of SD423 was analyzed and was identical to the Chinese, European and Indian strains; There is a large difference with the attenuated strain DEV K p63 ( Zou et al, 2014 ), SD423 has a 529 bp insertion after 281 bp.…”
Section: Discussionmentioning
confidence: 99%